Doctors with problems in an NHS workforce. - Donaldson, L. J. (BMJ Group, 1994)
OBJECTIVES--To describe the incidence, nature, and implications of serious disciplinary problems among the medical staff of a large NHS hospital workforce. DESIGN--Descriptive study with analysis of case records. SETTING--Northern Health Region, an administrative area within the NHS covering a population of three million. SUBJECTS--Forty nine hospital doctors: 46 consultants and three associate specialists. MAIN OUTCOME MEASURES--The nature of the problems encountered within the doctors' practice, and the types of action taken by the employing authority. RESULTS--Over a five year period concerns serious enough to warrant the consideration of disciplinary action were raised about 6% of all senior medical staff (49/850). Ninety six types of problem were encountered, and were categorised as poor attitude and disruptive or irresponsible behaviour (32), lack of commitment to duties (21), poor skills and inadequate knowledge (19), dishonesty (11), sexual matters (seven), disorganised practice and poor communication with colleagues (five), and other problems (one). Twenty five of the 49 doctors retired or left the employer's service, whereas 21 remained in employment after counselling or under supervision. CONCLUSIONS--Existing procedures for hospital doctors within the NHS are inadequate to deal with serious problems. Dealing with such problems requires experience, objectivity, and a willingness to tolerate unpleasantness and criticism. Because most consultants' contracts are now held by NHS trust hospitals, however, those who had developed skill over the years in handling these complex issues are now no longer involved.